Ecosystem-Based Marine Fisheries Management Model for Resource Sustainability - Muhammad Anjas Rahman; Rivan Syahfana; Artha Margian Saputra (Journal of Marine Fisheries, 2025)
Marine fisheries face increasing pressure from overexploitation, climate variability, and ecosystem degradation. Conventional single-species management approaches have proven insufficient to address these complex challenges. Ecosystem-Based Fisheries Management (EBFM) has emerged as an integrated framework that considers ecological, environmental, economic, and social dimensions of fisheries systems. This study aims to develop a conceptual model of ecosystem-based marine fisheries management to support long-term resource sustainability. The study applied a qualitative systematic review combined with comparative analysis of empirical EBFM case studies from tropical and temperate marine ecosystems. Data were collected from peer-reviewed international and national journals published between 2008 and 2025. The analysis focused on ecosystem indicators, management domains, governance mechanisms, and adaptive strategies. The results show that effective EBFM models consistently integrate habitat protection, biodiversity monitoring, stakeholder participation, and climate-responsive management tools. Tropical fisheries require stronger emphasis on spatial planning and community-based governance due to high ecological sensitivity and socio-economic dependence. The proposed model synthesizes ecological thresholds, adaptive management cycles, and participatory decision-making processes. This model provides a practical framework for policymakers and fisheries managers to enhance resilience and sustainability of marine fisheries systems. The study contributes to the operationalization of EBFM in developing country contexts.